SiC-reinforced CrMnFeCoNi high-entropy alloy composite material and preparation method thereof
The SiC-enhanced CrMnFeCoNi high-entropy alloy composite was prepared by step-by-step ball milling process and vacuum hot press sintering process, which solved the problems of poor matching of high-entropy alloy strength and plasticity and the reaction of SiC with high-entropy alloy to generate brittle carbides, and achieved high strength and good ductility of the composite.
Patent Information
- Application Number
- CN202510038961.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-18
AI Technical Summary
CrMnFeCoNi high-entropy alloy has poor strength and plasticity matching at room temperature, and SiC ceramic particles react with the high-entropy alloy matrix to generate brittle carbides, weakening the material ductility.
The CrMnFeCoNi high-entropy alloy powder was pre-ball milled by step-by-step ball milling to form a fine crystal reinforcement layer, and then SiC powder was added to reduce the physical contact area, suppress the generation of brittle phases, and SiC enhanced CrMnFeCoNi high-entropy alloy composite material was prepared by vacuum hot press sintering process.
The strength and elongation of the composite material are significantly improved, the negative impact of brittleness relative to the material ductility is reduced, and the comprehensive mechanical properties of the composite material are maintained at a relatively excellent level.
Smart Images

Figure CN119843135A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials and preparation thereof, and relates to a SiC reinforced CrMnFeCoNi high entropy alloy composite material and a preparation method thereof. Background Art
[0002] High entropy alloys are alloys formed by five or more metals in equal or approximately equal amounts. Single-phase face-centered cubic CrMnFeCoNi high entropy alloys have great application potential in aerospace, cryogenic equipment, transportation and other fields due to their good mechanical properties at room temperature and low temperature, and have attracted widespread attention. However, compared with the excess ductility of CrMnFeCoNi high entropy alloys, their yield strength and ultimate tensile strength are relatively low, and the poor matching of strength and plasticity limits their practical applications.
[0003] Research has found that introducing nano-scale strengthening phases, such as ceramic particles (such as SiC, TiC, WC, etc.), is an effective way to improve the room temperature strength of high entropy alloys. However, in practical applications, the C element easily reacts with the elements (especially Cr) in the CrMnFeCoNi high entropy alloy matrix to form large-sized carbides (such as M 23 C 6 Although these large-sized carbides can improve the strength of the alloy to a certain extent, due to their brittle characteristics, they often significantly weaken the ductility of the alloy material, resulting in a significant negative impact on the overall mechanical properties of the material.
[0004] Therefore, it is necessary to provide a SiC reinforced CrMnFeCoNi high-entropy alloy composite material and a preparation method thereof, so as to effectively improve the strength of the composite material and reduce the negative impact of brittleness on the ductility of the composite material, so as to maintain the comprehensive mechanical properties of the composite material at a good level and enable the composite material to meet more application requirements. Summary of the invention
[0005] In order to overcome the problems in the background technology, the present invention proposes a SiC-enhanced CrMnFeCoNi high entropy alloy composite material and a preparation method thereof. The CrMnFeCoNi high entropy alloy powder is pre-milled by a step-by-step ball milling process to form a fine-grained strengthening layer on its surface. After that, SiC powder is added. When the harder SiC powder contacts the CrMnFeCoNi high entropy alloy matrix, it is not easy to penetrate into the matrix, thereby reducing the physical contact area and inhibiting the generation of harmful brittle phases. In addition, SiC is retained in the SiC-enhanced CrMnFeCoNi high entropy alloy composite material prepared by the present invention, which helps to significantly improve the material strength. At the same time, a bimodal grain structure is constructed in the composite material, and micro-nano enhancement is achieved, so that the comprehensive mechanical properties of the composite material are maintained at a relatively excellent level.
[0006] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0007] On one hand, the present invention provides a SiC reinforced CrMnFeCoNi high entropy alloy composite material. The composite material comprises, by mass fraction, CrMnFeCoNi high entropy alloy: 95-99.5%, SiC: 0.5-5%.
[0008] Preferably, the CrMnFeCoNi high entropy alloy composition includes Cr, Mn, Fe, Co, and Ni, wherein the atomic ratio of Cr, Mn, Fe, Co, and Ni is 1:1:1:1:1.
[0009] Another aspect of the present invention provides a method for preparing the composite material, the method comprising the following steps:
[0010] S1: ball milling CrMnFeCoNi high entropy alloy powder under argon atmosphere;
[0011] S2: adding SiC powder to the CrMnFeCoNi high entropy alloy powder after ball milling in step S1, and continuing ball milling under argon atmosphere to obtain a composite material powder;
[0012] S3: vacuum hot pressing and sintering the composite material powder obtained in step S2 to obtain a SiC reinforced CrMnFeCoNi high entropy alloy composite material block.
[0013] Preferably, in step S1, the purity of the CrMnFeCoNi high entropy alloy powder is ≥99.95%, and the average particle size is 10-25 um.
[0014] Preferably, in step S1, the ball milling medium is stainless steel grinding balls, the ball-to-material ratio of the ball milling mixture is 5:1-10:1, the rotation speed is 150-250 r / min, and the time is 30-40 h.
[0015] Preferably, in step S1, stearic acid is added during ball milling, and the mass of the stearic acid added is 0.5% of the mass of the CrMnFeCoNi high entropy alloy powder.
[0016] Preferably, in step S2, the purity of SiC powder is ≥99.9% and the average particle size is 20-40 nm.
[0017] Preferably, in step S2, after adding SiC powder, ball milling is continued for 5 to 10 hours.
[0018] Preferably, in step S3, the temperature of vacuum hot pressing sintering is 950-1050° C., the pressure is 40-50 MPa, and the holding time is 0.5-1 h.
[0019] Preferably, in step S3, the vacuum degree is less than 1×10 -1 Pa, vacuum hot pressing sintering heating rate is 8~
[0020] 10℃ / min.
[0021] Beneficial effects of the present invention:
[0022] The present invention pre-ball-mills the CrMnFeCoNi high entropy alloy powder through a step-by-step ball-milling process to form a fine-grained strengthening layer on its surface. When the harder SiC powder contacts the CrMnFeCoNi high entropy alloy, it is not easy to penetrate into the matrix, thereby reducing the physical contact area, which is beneficial to inhibiting the generation of harmful brittle phases, reducing the negative impact of brittle phases on the composite material, and contributing to improving the comprehensive mechanical properties of the composite material. At the same time, SiC is retained in the composite material of the present invention, the material strength is improved, and a bimodal grain structure is constructed in the composite material to achieve micro-nano enhancement. Finally, the comprehensive mechanical properties of the composite material are maintained at a relatively excellent level, and the application scope of the composite material is expanded. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The morphologies and element distribution diagrams of the composite material powders prepared in Example 1 and Comparative Example 2, wherein (a) is the morphology diagram of the composite material powder of Example 1, and (b) is the morphology diagram of the composite material powder of Comparative Example 2.
[0024] Figure 2 This is a bimodal grain distribution diagram of the composite material prepared by the present invention;
[0025] Figure 3 The true stress-strain curves of Examples 1, 2, 3 and Comparative Examples 1 and 2 are shown; DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the described contents.
[0027] Example 1
[0028] (1) CrMnFeCoNi high entropy alloy powder was placed in a stainless steel bottle, stainless steel grinding balls were added, the ball-to-material ratio was 10:1, 0.5% stearic acid by mass of the CrMnFeCoNi high entropy alloy powder was added, the speed was 200 r / min, and the ball milling was carried out in an argon atmosphere for 40 h.
[0029] (2) Add SiC powder to the ball-milled CrMnFeCoNi high entropy alloy powder (after adding SiC powder, the mass of SiC powder accounts for 1% of the total mass of CrMnFeCoNi high entropy alloy powder and SiC powder), and then continue ball milling under argon atmosphere for 10 hours to obtain a composite material powder.
[0030] (3) The prepared composite material powder is placed in a graphite mold and subjected to vacuum hot pressing sintering. Before vacuum hot pressing sintering, the vacuum is evacuated to a vacuum degree of <1×10 -1 Pa, maintaining the pressure at 50 MPa, heating from room temperature to 1050 °C at a heating rate of 10 °C / min, and keeping the temperature for 1 h to obtain a composite material block.
[0031] The microscopic morphology of the composite material powder prepared in this example was observed, and the element distribution of the composite material powder was detected, and the results were as follows: Figure 1 shown.
[0032] The stress and strain test results of the composite material block prepared in this example are as follows: Figure 3 shown.
[0033] Example 2
[0034] (1) CrMnFeCoNi high entropy alloy powder was placed in a stainless steel bottle, stainless steel grinding balls were added, the ball-to-material ratio was 5:1, stearic acid (0.5% by weight of the CrMnFeCoNi high entropy alloy powder) was added, the rotation speed was 250 r / min, and the ball milling was carried out for 35 h in an argon atmosphere.
[0035] (2) Add SiC powder to the ball-milled CrMnFeCoNi high entropy alloy powder (after adding SiC powder, the mass of SiC powder accounts for 0.5% of the total mass of CrMnFeCoNi high entropy alloy powder and SiC powder), and then continue ball milling under argon atmosphere for 10 hours to obtain a composite material powder.
[0036] (3) The prepared composite material powder is placed in a graphite mold and subjected to vacuum hot pressing sintering. Before vacuum hot pressing sintering, the vacuum is evacuated to a vacuum degree of <1×10 -1 Pa, maintaining the pressure at 40 MPa, heating from room temperature to 1000 °C at a heating rate of 8 °C / min, and keeping the temperature for 0.5 h to obtain a composite material block.
[0037] The stress and strain test results of the composite material block prepared in this example are as follows: Figure 3 shown.
[0038] Example 3
[0039] (1) CrMnFeCoNi high entropy alloy powder was placed in a stainless steel bottle, stainless steel balls were added, the ball-to-material ratio was 10:1, stearic acid (0.5% by weight of the CrMnFeCoNi high entropy alloy powder) was added, the rotation speed was 150 r / min, and ball milling was carried out in an argon atmosphere for 30 h.
[0040] (2) Add SiC powder to the ball-milled CrMnFeCoNi high entropy alloy powder (after adding SiC powder, the mass of SiC powder accounts for 5% of the total mass of CrMnFeCoNi high entropy alloy powder and SiC powder), and then continue ball milling under argon atmosphere for 5 hours to obtain a composite material powder.
[0041] (3) The prepared composite material powder is placed in a graphite mold and subjected to vacuum hot pressing sintering. Before vacuum hot pressing sintering, the vacuum is evacuated to a vacuum degree of <1×10 -1 Pa, maintaining the pressure at 50 MPa, heating from room temperature to 950 °C at a heating rate of 10 °C / min, and keeping the temperature for 1 h to obtain a composite material block.
[0042] Comparative Example 1
[0043] (1) CrMnFeCoNi high entropy alloy powder was placed in a stainless steel bottle, stainless steel grinding balls were added, the ball-to-material ratio was 10:1, 0.5% stearic acid by mass of the CrMnFeCoNi high entropy alloy powder was added, the rotation speed was 200 r / min, and the ball milling was carried out in an argon atmosphere for 50 h.
[0044] (2) The obtained high entropy alloy powder is placed in a graphite mold and subjected to vacuum hot pressing sintering. Before vacuum hot pressing sintering, the vacuum is evacuated to a vacuum degree of <1×10 -1 Pa, maintaining the pressure at 50 MPa, heating from room temperature to 1050 °C at a heating rate of 10 °C / min, and keeping the temperature for 1 h to obtain a high entropy alloy block.
[0045] The stress and strain test of the high entropy alloy block prepared in this comparative example is as follows: Figure 3 shown.
[0046] Comparative Example 2
[0047] (1) CrMnFeCoNi high entropy alloy powder and SiC powder were placed in a stainless steel bottle (the mass of SiC powder accounted for 1% of the total mass of CrMnFeCoNi high entropy alloy powder and SiC powder), stainless steel grinding balls were added, the ball-to-material ratio was 10:1, and 0.5% of stearic acid by mass of CrMnFeCoNi high entropy alloy powder was added. The speed was 200 r / min, and ball milling was carried out for 50 h in an argon atmosphere to obtain a composite material powder.
[0048] (2) The prepared composite material powder is placed in a graphite mold and subjected to vacuum hot pressing sintering. Before vacuum hot pressing sintering, the vacuum is evacuated to a vacuum degree of <1×10 -1 Pa, maintaining the pressure at 50 MPa, heating from room temperature to 1050 °C at a heating rate of 10 °C / min, and keeping the temperature for 1 h to obtain a composite material block.
[0049] The microscopic morphology of the composite material powder prepared in this example was observed, and the element distribution of the composite material powder was detected, and the results were as follows: Figure 1 shown.
[0050] The stress and strain test results of the composite material block prepared in this example are as follows: Figure 3 shown.
[0051] pass Figure 1 It can be seen that the composite powder (Example 1, Figure 1 (a)) and the composite powder after one ball milling (Comparative Example 2, Figure 1 (b)) It can be seen from the comparison that in Example 1, the high entropy alloy powder is coated with SiC particles, while there are no SiC particles in the composite material powder in Comparative Example 2, but Si-rich regions appear. This shows that in the one-step ball milling process, SiC and the high entropy alloy powder are mechanically alloyed, and in the two-step ball milling process, the high entropy alloy powder is first pre-ground to harden its surface, and then SiC particles are added, thereby inhibiting alloying and retaining SiC. SiC particles, as an obstacle to dislocation movement, can produce dislocation accumulation and entanglement, thereby improving the strength of the material. At the same time, SiC particles usually have extremely high hardness and modulus. Therefore, when a component made of the composite material of the present invention is subjected to a load, part of the load can be transferred to these rigid particles, thereby improving the overall strength and hardness of the composite material.
[0052] pass Figure 2 It can be seen that a bimodal grain structure with coarse and fine grains coexisting appears in the composite material prepared by the present invention. This is because through process optimization, the two-step ball milling process allows SiC to be preserved in the matrix, and the fine SiC plays a role in pinning the grain boundaries, inhibiting the growth of grains in some areas, and finally obtaining a bimodal grain structure with coarse and fine grains staggered. Fine grains can improve the yield strength and tensile strength of the material by inhibiting dislocation movement, and coarse grains are more likely to undergo intracrystalline slip and grain rotation during deformation, thereby providing the material with greater ductility and deformation resistance, thereby synergistically improving the strength and plasticity of the material.
[0053] pass Figure 3 The quantitative data of yield strength, ultimate tensile strength and elongation of Examples 1-3 and Comparative Examples 1-2 are shown in Table 1.
[0054] Table 1
[0055] Yield strength (MPa) Ultimate tensile strength (MPa) Elongation(%) Example 1 617.73 983.25 9.84 Example 2 621.07 966.71 8.86 Example 3 623.23 1034.01 12.19 Comparative Example 1 430.59 888.65 18.50 Comparative Example 2 579.27 914.08 7.50
[0056] It can be seen from Table 1 that the yield strengths of Examples 1, 2, and 3 are 617.73, 621.07, and 623.23 MPa, respectively, and the yield strength of Comparative Example 1 is 430.59 MPa. The ultimate tensile strengths of Examples 1, 2, and 3 are 983.25, 966.71, and 1034.01 MPa, respectively, and the ultimate tensile strength of Comparative Example 1 is 888.65 MPa. It can be seen that the addition of SiC significantly improves the yield strength and ultimate tensile strength of the material.
[0057] It can be seen from Table 1 that the elongations of Examples 1-3 and Comparative Example 2 are all decreased relative to Comparative Example 1, indicating that when SiC is used as a strengthening phase, the situation that the C element reacts with the high entropy alloy matrix to generate a brittle phase cannot be completely avoided. Although the elongation of Examples 1-3 is reduced relative to Comparative Example 1, it is obvious that the degree of decrease in the elongation of Examples 1-3 relative to Comparative Example 1 is less than the degree of decrease in the elongation of Comparative Example 2 relative to Comparative Example 1, which fully illustrates that the composite material prepared by the present invention can effectively weaken the negative impact of the formation of brittle phase on the elongation of the composite material. Among them, compared with Comparative Example 1, the yield strength of Example 3 is increased by about 44.74%, the ultimate tensile strength is increased by about 16.36%, and the elongation is reduced by 6.31%. Compared with Comparative Example 1, the yield strength of Comparative Example 2 is increased by about 34.53%, the ultimate tensile strength is increased by about 2.86%, and the elongation is reduced by 11%. The composite material prepared by the present invention has more excellent comprehensive mechanical properties.
[0058] It can be seen from Table 1 that the yield strengths of Examples 1, 2, and 3 are 617.73, 621.07, and 623.23 MPa, respectively, and the yield strength of Comparative Example 2 is 579.27 MPa. The ultimate tensile strengths of Examples 1, 2, and 3 are 983.25, 966.71, and 1034.01 MPa, respectively, and the ultimate tensile strength of Comparative Example 2 is 914.08 MPa. The yield strength and ultimate tensile strength of Comparative Example 2 are both lower than those of Examples 1-3. And the elongation of Comparative Example 2 is 7.50%, which is lower than 9.84%, 8.86%, and 12.19% of Examples 1, 2, and 3. It can be seen that the strength and elongation of the material are synergistically improved through the step-by-step ball milling process.
[0059] In summary, the composite material prepared by the present invention can effectively reduce the negative impact of brittleness on the ductility of the composite material, while significantly improving the yield strength and ultimate tensile strength of the composite material, so that the overall performance of the composite material shows an upward trend, allowing the composite material to maintain relatively excellent comprehensive performance.
[0060] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A SiC reinforced CrMnFeCoNi high entropy alloy composite material, characterized in that: The composite material comprises, by mass fraction, 95-99.5% of CrMnFeCoNi high entropy alloy and 0.5-5% of SiC.
2. A SiC reinforced CrMnFeCoNi high entropy alloy composite material according to claim 1, characterized in that: The CrMnFeCoNi high entropy alloy composition includes Cr, Mn, Fe, Co, and Ni, wherein the atomic ratio of Cr, Mn, Fe, Co, and Ni is 1:1:1:1:
1.
3. The method for preparing the SiC reinforced CrMnFeCoNi high entropy alloy composite material according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: S1: ball milling CrMnFeCoNi high entropy alloy powder under argon atmosphere; S2: adding SiC powder to the CrMnFeCoNi high entropy alloy powder after ball milling in step S1, and continuing ball milling under argon atmosphere to obtain a composite material powder; S3: vacuum hot pressing and sintering the composite material powder obtained in step S2 to obtain a SiC reinforced CrMnFeCoNi high entropy alloy composite material block.
4. The preparation method according to claim 3, characterized in that: In the step S1, the purity of the CrMnFeCoNi high entropy alloy powder is ≥99.95%, and the average particle size is 10-25 um.
5. The preparation method according to claim 3, characterized in that: In the step S1, the ball milling medium is stainless steel grinding balls, the ball-to-material ratio of the ball milling mixture is 5:1-10:1, the rotation speed is 150-250 r / min, and the time is 30-40 hours.
6. The preparation method according to claim 3, characterized in that: In the step S1, stearic acid is added during ball milling, and the mass of the stearic acid added is 0.5% of the mass of the CrMnFeCoNi high entropy alloy powder.
7. The preparation method according to claim 3, characterized in that: In the step S2, the purity of the SiC powder is ≥99.9%, and the average particle size is 20-40 nm.
8. The preparation method according to claim 3, characterized in that: In the step S2, after adding SiC powder, the ball milling is continued for 5 to 10 hours.
9. The preparation method according to claim 3, characterized in that: In the step S3, the temperature of vacuum hot pressing sintering is 950-1050° C., the pressure is 40-50 MPa, and the holding time is 0.5-1 h.
10. The preparation method according to claim 3, characterized in that: In step S3, the vacuum degree is less than 1×10 -1 Pa, the vacuum hot pressing sintering heating rate is 8-10℃ / min.
Citation Information
Cited By
High-temperature wear-resistant high-entropy alloy-based composite coating and preparation method thereof
CN120796813A